EFFECTS OF PROTEIN-DEFICIENCY AND NATURAL INTESTINAL INFECTION WITH GIARDIA-LAMBLIA ON JEJUNAL INTRAEPITHELIAL LYMPHOCYTES IN RATS OF DIFFERENT AGES - Rodrigues, MAM; Decarvalho, MFG; Montenegro, M. R. (Associação Brasileira de Divulgação Científica (ABRADIC), 1994)
1. The interaction between experimental protein deprivation and natural intestinal infection by Giardia lamblia was studied in terms of its effects on the intraepithelial lymphocyte (IEL) population and morphology of the jejunal mucosa of rats of different ages.2. Young, adult and old male Wistar rats received a protein-deficient diet (2% casein) or a control diet (20% casein) for 42 days. Mucosal height and the number of lymphocytes located among 500 consecutive epithelial cells (EC) along the villi or crossing the basement membrane were determined in PAS-stained jejunal fragments.3. The number of IEL increased progressively with animal age, from 14 to 25 per 100 epithelial cells, with significant differences between age ranges. However, the number of IEL did not differ between control and protein-deficient rats in any of the age groups. The proportion of lymphocytes crossing the basement membrane was approximately two-fold greater in young (2.8/100 EC) and adult (5.8/100 EC) protein-deficient animals than in their respective controls (1.6 and 2.8/100 EC). The intensity of parasite colonization was moderate, from 3 to 5/100 EC and did not differ between groups. The pattern of morphologic changes of jejunal mucosa in protozoal infection did not differ between control and protein-deficient animals in any of the three age groups.4. We conclude that intestinal infection with Giardia lamblia probably stimulated the local immune response, masking the reduction of the IEL population induced by protein deficiency. The increase in lymphocyte numbers with age may be related to prolonged antigenic stimulation promoted by infection.
Keywords: GIARDIA LAMBLIA INFECTION; JEJUNAL INTRAEPITHELIAL LYMPHOCYTES; PROTEIN DEFICIENCY